Prioritising nutrition in order to achieve the Millennium Development Goals in India - Kumar, V (Young Lives, 2012)
Malnutrition causes long-term damage to children’s development, with huge social and economic costs. It affects not only children’s physical development but also their cognitive development, so reducing future productivity and leading ultimately to economic loss for the nation as a whole. India has recorded strong economic growth in recent years but has shown little progress in tackling malnutrition. It is evident that economic growth alone will not solve the malnutrition problem and sustaining growth will require human capital development. Young Lives research suggests that there has been very little improvement over the last decade in children’s nutritional status and demonstrates the impact of malnutrition on children’s later development. Strengthening services and social protection schemes such as ntegrated Child Development Services, the Public Distribution System and the Midday Meal Scheme are important elements of securing better nutrition for children and will support progress towards the Millennium Development Goals.